2021
DOI: 10.5194/wcd-2-675-2021
|View full text |Cite
|
Sign up to set email alerts
|

Linking air stagnation in Europe with the synoptic- to large-scale atmospheric circulation

Abstract: Abstract. The build-up of pollutants to harmful levels can occur when meteorological conditions favour their production or accumulation near the surface. Such conditions can arise when a region experiences air stagnation. The link between European air stagnation, air pollution and the synoptic- to large-scale circulation is investigated in this article across all seasons and the 1979–2018 period. Dynamical indices identifying atmospheric blocking, Rossby wave breaking, subtropical ridges, and the North Atlanti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 71 publications
(139 reference statements)
1
11
0
Order By: Relevance
“…This index considers a day as stagnant when three conditions are simultaneously fulfilled within a grid cell: near-surface wind speed <3.2 m s −1 , 500 hPa wind speed <13.0 m s −1 , and accumulated precipitation <1.0 mm. Previous analyses have found that this formulation of the ASI outperforms others in capturing the links among large-scale circulation, stagnation, and air pollution in Europe (Garrido-Perez et al 2021, Maddison et al 2021). This index is also commonly used for air pollution studies in the U.S. (Schnell andPrather 2017, Sun et al 2017).…”
Section: Air Stagnation Indexmentioning
confidence: 95%
See 1 more Smart Citation
“…This index considers a day as stagnant when three conditions are simultaneously fulfilled within a grid cell: near-surface wind speed <3.2 m s −1 , 500 hPa wind speed <13.0 m s −1 , and accumulated precipitation <1.0 mm. Previous analyses have found that this formulation of the ASI outperforms others in capturing the links among large-scale circulation, stagnation, and air pollution in Europe (Garrido-Perez et al 2021, Maddison et al 2021). This index is also commonly used for air pollution studies in the U.S. (Schnell andPrather 2017, Sun et al 2017).…”
Section: Air Stagnation Indexmentioning
confidence: 95%
“…We define air stagnation using the National Climate Data Center Air Stagnation Index (ASI; Wang and Angell 1999) adaptation by Horton et al (2012), a commonly used metric in air quality meteorology studies (Leung and Gustafson 2005, Horton et al 2012, 2014, Huang et al 2017, Maddison et al 2021. This index considers a day as stagnant when three conditions are simultaneously fulfilled within a grid cell: near-surface wind speed <3.2 m s −1 , 500 hPa wind speed <13.0 m s −1 , and accumulated precipitation <1.0 mm.…”
Section: Air Stagnation Indexmentioning
confidence: 99%
“…The resulting number of predictors ranges from two to seven and is around five on average over the whole domain for all pollutants. The stepwise algorithm employed in this study is the same as in Garrido-Perez et al (2021) and Maddison et al (2021) (see details in their methods sections). This algorithm ensures noncollinearity between the explanatory variables, which is an essential assumption of MLRMs.…”
Section: Statistical Modelmentioning
confidence: 99%
“…While anthropogenic emissions are the main source of air pollutants, observational studies have illustrated that the variability of their concentrations is closely related to changes in weather conditions (Fiore et al, 2015). In particular, the dependence of air pollution on the largescale circulation has been subject of comprehensive analyses (Pausata et al, 2013;Chang et al, 2016;Webber et al, 2017;Xu et al, 2017;Ordóñez et al, 2019;Maddison et al, 2021). Recent reports have evidenced that air pollution over Europe is quite sensitive to the location of anticyclonic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the drivers of air stagnation events can provide information that may be beneficial for seasonal forecasting and climate change projections, where directly identifying air stagnation or pollution extremes can be challenging. Surface weather conditions in Europe, including air stagnation, are strongly governed by the synopticto large-scale circulation over the region (Gaetani et al 2011, Mahlstein et al 2012, Santos et al 2013, Maddison et al 2021. Air stagnation has been linked to the North Atlantic-European atmospheric circulation (Maddison et al 2021) through circulation features associated with high pressure systems, such as blocks (Hamburger et al 2011, Garrido-Perez et al 2017, Vautard et al 2018, Rossby wave breaking (Webber et al 2017), and subtropical ridges (Ordó nez et al 2017, Maddison et al 2021).…”
Section: Introductionmentioning
confidence: 99%